Organizational climate and performance of primary teachers in the I.E. “Manuel Seoane Corrales”, Mi Peru district, Callao Region - Guerrero Obregón, Ruth Noemí (2023)
The current research, titled "Organizational Climate and Teacher Performance at the Manuel Seoane Corrales Educational Institution", had as its main objective to examine the relationship between the organizational environment and teacher performance. To achieve this purpose, a cross-sectional correlational design research approach was chosen. Two questionnaires were used as data collection instruments, one corresponding to each variable under study. The sample consisted of a group of 40 teachers who teach at the primary level of said institution. Regarding information processing, after creating the corresponding database, frequency distribution tables and contingency tables were prepared to present the results appropriately. At the conclusion of this study, it was found that, in the context of the current research, a significant correlation was not established between the organizational climate and teaching performance at the Manuel Seoane Corrales Educational Institution. This result contrasts with previous research that has explored this same relationship in various educational settings. Regarding the organizational climate, a level considered 'Low' was observed on 20 occasions, which is equivalent to 50%, while teaching performance was rated as 'Moderate' in 19 cases, representing 47.5% of the total cases analyzed.